Modeling of static var compensator-high voltage direct current to provide power and improve voltage profile - Javadian, Abdolmajid; Zadehbagheri, Mahmoud; Kiani, Mohammad Javad; Nejatian, Samad; Sutikno, Tole (Institute of Advanced Engineering and Science, 2021)
Transmission lines react to an unexpected increase in power, and if these power changes are not controlled, some lines will become overloaded on certain routes. Flexible alternating current transmission system (FACTS) devices can change the voltage range and phase angle and thus control the power flow. This paper presents suitable mathematical modeling of FACTS devices including static var compensator (SVC) as a parallel compensator and high voltage direct current (HVDC) bonding. A comprehensive modeling of SVC and HVDC bonding in the form of simultaneous applications for power flow is also performed, and the effects of compensations are compared. The comprehensive model obtained was implemented on the 5-bus test system in MATLAB software using the Newton-Raphson method, revealed that generators have to produce more power. Also, the addition of these devices stabilizes the voltage and controls active and reactive power in the network.